Pengaruh Tax Holiday, Tax Allowance, dan Tarif Pajak Terhadap Investasi Asing di Sektor Manufaktur Analisis Data Panel Periode 2019 – 2024 - Na’ila Robiihah Salsabila; Setyo Mahanani (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the influence of tax holiday, tax allowance, and tax rate policies on foreign investment in Indonesia’s manufacturing sector during the period 2019–2024. The research employs panel data analysis using the Fixed Effect Model and Random Effect Model approaches. The results show that tax holiday and tax allowance incentives have a significant positive effect on foreign investment, while tax rates have a negative effect. These findings highlight the importance of fiscal incentives in attracting foreign investment to the manufacturing sector. This research is expected to provide input for policymakers in formulating more effective tax policies to encourage investment and national economic growth.